FERMENTASI NIRA SORGUM MANIS MENJADI ETANOL (ALCOHOLIC FERMENTATION OF SWEET SORGHUM JUICE) - Aris Toharisman; Hendro Santoso (Jurnal Kimia Terapan Indonesia, 1998)
Sweet sorghum juice about 11-16% of total sugar, and so it could be potentially fermenled to produce ethanol. The concentrated juices were used as media for ethanol production in batch culture using Saccharomyces cerevisiae R5 at 30°C and pH 4.5. The ethanol yield (Yp/s ) and volumetric productivity during 48 hours of fermentation lime with 20.08%(x/v) initial sugar contents were 0.44 g.g-1 and O.18 g.1-1.h-1,respectively.Keywords : Alcholic fermentation, sweet sorghum juices, cane molasses, S. cerevisiae, and batch culture.